Sorotan terpilih dalam sejarah Malaysia esei sumbangsih kepada Dr. Cheah Boon Kheng - Mahani Musa; Tan, Liok Ee (Penerbit Universiti Sains Malaysia bagi pihak Pusat Pengajian Ilmu Kemanusiaan, 2000)
History of Malaysia and its social conditions during the Japanese occupation; festschrift in honor of Cheah Boon Kheng, former associate professor at Universiti Sains Malaysia.